VALIDATION OF 6-MERCAPTOPURINE AND 6-THIOGUANINE IN DRIED BLOOD SPOT BY ULTRA PERFORMANCE LIQUID CHROMATOGRAPHY-TANDEM MASS SPECTROMETRY - Harahap, Yahdiana; Astrini, Cheputri Rahma; Suryadi, Herman (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to obtain an optimal and validated method of analyzing 6-mercaptopurine (6-MP) and 6-thioguanine (6-TG) simultaneously in dried blood spot samples using ultra high-performance liquid chromatography-tandem mass spectrometry. Method: Separation was performed with a 1.7-μm amide column, which had a mobile phase with a flow rate of 0.2 mL/min and comprised 0.2% formic acid in water, 0.1% formic acid in acetonitrile, and methanol with a gradient elution. Detection was performed using Waters Xevo TQD. Result: This method was linear with a range of 25–1000 ng/mL for 6-MP and 6-TG, with consecutive r values of ≥0.996 and ≥0.995, respectively. The intra- and inter-day % difference value and coefficient of variation for the accuracy and precision were not more than 15% and 20%, respectively, at a concentration lower limit of quantitation. Conclusion: This method fulfilled the requirements of the European Medicines Agency guideline for validation.